Upaya Meningkatkan Kemampuan Kognitif Pada Anak usia Dini Melalui Media Bahan Alam Kelompok B di KB Cahaya Harapan - fatmawati, fatmawati; Yanti, Yanti (Institut Agama Islam Ngawi, 2025)
The purpose of this study was to determine the natural materials that can be used to improve children’s cognitive abilities and to determine how to improve children’s cognitive abilities in KB Cahaya Harapan Karendan village.Through the classroom action research method.The techniques and data collection tools used in this study were direct observation,interviews with parents and educators and documentation.The source of this study was KB Cahaya Harapan in Karendan village.The results of this study indicate that through natural material media,it can be used to develope children’s cognitive abilities,namely by introducing the concept of shape,appearance,color and size of the object.where through the results of this study showed that there was a lot of improvement in cognitive abilities through the use of natural material media reaching an average in the first cycle and increasing even more in the second cycle.In this case,it shows that teachers can utilize the natural surroundings in the environment around the KB Cahaya Harapan educational institution as an alternative to overcome the limitation of media in our institution.Where in this case it can also explore how interaction with natural elements can affect childrent’s cognitive development.The results showed that exposure to nature significantly increased children’s critical thinking skills and creativity.in conclusion,natural material media can be an effective tool in supporting children’s learning and cognitive development.Keywords: Natural Materials, KB Cahaya Harapan, Cognitive Ability, AUD Development